VBM Reveals Brain Volume Differences between Parkinson’s Disease and Essential Tremor Patients - Lin, Ching-Hung; Chen, Chun-Ming; Lu, Ming-Kuei; Tsai, Chon-Haw; Chiou, Jin-Chern; Liao, Jan-Ray; Duann, Jeng-Ren (Frontiers in Human Neuroscience, 2013)
Symptoms of essential tremor (ET) are similar to those of Parkinson’s disease (PD) during their initial stages. Presently, there are few stable biomarkers available on a neuroanatomical level for distinguishing between these two diseases. However, few investigations have directly compared the changes in brain volume and assessed the compensatory effects of a change in the parts of the brain associated with PD and with ET. To determine the compensatory and/or degenerative anatomical changes in the brains of PD and ET patients, the present study tested, via two VBM approaches (Basic vs. Dartel VBM processing), the anatomical brain images of 10 PD and 10 ET patients, as well as of 13 age-matched normal controls, obtained through a 3T magnetic resonance scanner. These findings indicate that PD and ET caused specific patterns of brain volume alterations in the brains examined. In addition, our observations also revealed compensatory effects, or self-reorganization, occurring in the thalamus and the MTG in the PD and ET patients, due perhaps in part to the enhanced thalamocortical sensorimotor interaction and the head-eye position readjustment, respectively, in these PD and ET patients. Such a distinction may lend itself to use as a biomarker for differentiating between these two diseases.